ANDROLOGY ASPECTS OF AID CHILDLESS COUPLES. - V. A. Bozhedomov (Вестник урологии, 2015)
The article is devoted to clinical and organizational aspects in helping childless couples with the supposed male factor. A three-stage system for curative-diagnostic process is proposed by the authors. Modern demands to the equipment of andrologic laboratories and to the techniques of sperm quality evaluation are described. The authors have backgrounded their idea to have a three-stage complex prophylactics of reproductive function disorders in males.